Biomimetic Redox-Responsive Mesoporous Organosilica Nanoparticles Enhance Cisplatin-Based Chemotherapy - Chen, Fangman; Zhang, Fan; Wang, Yanbin; Peng, Jiahui; Cao, Lei; Mei, Qian; Ge, Mingfeng; Li, Li; Chen, Meiwan; Dong, Wen-fei; Chang, Zhimin (Frontiers in Bioengineering and Biotechnology, 2022)
Cisplatin-based chemotherapy is dominated in several cancers; however, insufficient therapeutic outcomes and systemic toxicity hamper their clinical applications. Controlled release of cisplatin and reducing inactivation remains an urgent challenge to overcome. Herein, diselenide-bridged mesoporous organosilica nanoparticles (MON) coated with biomimetic cancer cell membrane were tailored for coordination responsive controlled cisplatin delivery and GSH depletion to strengthen Pt-based chemotherapy. Cisplatin-loaded MON (MON-Pt) showed high loading capacity due to robust coordination between selenium and platinum atoms and preventing premature leakage in normal tissue. MON-Pt exhibited a controlled release of activated cisplatin in response to the redox tumor microenvironment. Meanwhile, MON-Pt containing redox-responsive diselenide bonds could efficiently scavenge intracellular inactivation agents, such as GSH, to enhance Pt-based chemotherapy. 4T1 breast cancer cell membranes cloaked MON-Pt (MON-Pt@CM) performed efficient anticancer performance and low in vivo system toxicity due to long blood circulation time and high tumor accumulation benefiting from the tumor targeting and immune-invasion properties of the homologic cancer cell membrane. These results suggest a biomimetic nanocarrier to control release and reduce the inactivation of cisplatin for efficient and safe Pt-based chemotherapy by responding and regulating the tumor microenvironment.